HEALTH LITERACY OF STUDENTS OF PROFESSIONAL STUDIES IN HEALTH ORIENTATION - Aleksandric, Jelena (PONS - medicinski časopis, 2024)
According to the definition of the World Health Organization, health literacy includes the cognitive and social skills and capacities needed to access, understand and use information in a way that promotes and protects good health. Reproductive health is a state of complete physical, mental and social well-being, and not merely the absence of disease or infirmity, in all matters relating to the reproductive system and its functions and processes. Objective: The main objective of this research was to determine whether and to what extent the level of health literacy affects the reproductive health of young people. Material and methods: The research belongs to the group of epidemiological studies, conducted according to the type of cross-sectional study. It was carried out in the period from 01. To 17.06.2019. A total of 230 students of professional health studies participated in the research. The questionnaire, in addition to demographic data, contained the S-TOFHLA health literacy test and specially designed questions about reproductive health. Results: Our research showed that six respondents (2.61%) had inadequate health literacy, 80 (34.78%) had marginal health literacy, and 144 (62.61%) had adequate health literacy. literacy. Greater health literacy is associated with sexual activity, number of partners, use of anti-baby pills. Discussion: Health literacy is influenced by many factors, including knowledge of reproductive health, age, gender, sociodemographic factors, economic status, level of education, and more. Insufficient promotion of sexual education in our society, potential mistrust in the official education system and the desire of respondents to independently research this area. Conclusion: More than two thirds of students show the adequate level of health literacy. Students who are older in terms of age and years of study have a higher level of health literacy. This research can serve as a starting point for the creation of new programs on reproductive health and health literacy, especially those aimed at the population of health professionals.